2016
DOI: 10.1088/1361-6463/aa5065
|View full text |Cite
|
Sign up to set email alerts
|

Tm3+, Yb3+activated ANbO4(A  =  Y, Gd, La) phosphors: a comparative study of optical properties (downshifting and upconversion emission) and laser induced heating effect

Abstract: A comparative study of optical properties and laser induced heating effects in Tm 3+ , Yb 3+ doped YNbO 4 , GdNbO 4 and LaNbO 4 phosphors is presented in this work. The phosphors were structurally characterized by x-ray diffraction and scanning electron microscopy measurements. The vibrational structures of the phosphors were studied using FTIR measurements. The optical band gaps (E g), calculated from the Wood and Tauc plot, are found to be 3.78, 4.50 and 3.27 eV for YNbO 4 , GdNbO 4 and LaNbO 4 , respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Each spectrum can be divided into two parts. The first part comprises of a strong and broad band located at 200‐300 nm originating from the absorption of NbO44-, which indicates that there is an efficient energy transfer from NbO44- groups to Sm 3+ . The second part ranging from 300 to 550 nm contains a series of sharp peaks corresponding to the transitions 6 H 5/2 to 3 H 7/2 (350 nm), 4 F 9/2 (367 nm), 4 D 5/2 (379 nm), 4 K 11/2 (408 nm), 4 P 5/2 / 4 M 19/2 (420 nm), 4 G 9/2 / 4 I 15/2 (442 nm), 4 F 5/2 / 4 I 13/2 (468 nm), 4 I 11/2 / 4 M 15/2 (483 nm), 4 F 3/2 (500 nm), and 4 G 5/2 (526 nm) of Sm 3+ ion, respectively …”
Section: Resultsmentioning
confidence: 99%
“…Each spectrum can be divided into two parts. The first part comprises of a strong and broad band located at 200‐300 nm originating from the absorption of NbO44-, which indicates that there is an efficient energy transfer from NbO44- groups to Sm 3+ . The second part ranging from 300 to 550 nm contains a series of sharp peaks corresponding to the transitions 6 H 5/2 to 3 H 7/2 (350 nm), 4 F 9/2 (367 nm), 4 D 5/2 (379 nm), 4 K 11/2 (408 nm), 4 P 5/2 / 4 M 19/2 (420 nm), 4 G 9/2 / 4 I 15/2 (442 nm), 4 F 5/2 / 4 I 13/2 (468 nm), 4 I 11/2 / 4 M 15/2 (483 nm), 4 F 3/2 (500 nm), and 4 G 5/2 (526 nm) of Sm 3+ ion, respectively …”
Section: Resultsmentioning
confidence: 99%
“…3 shows the UC emission behavior of the rare earth (Ho 3+ /Yb 3+ and Tm 3+ /Yb 3+ ) doped YNbO 4 , GdNbO 4 and LaNbO 4 phosphors in the visible region on excitation with a 980 nm diode laser. 25,[28][29][30] Intense green and moderately weak red emissions are observed in the GdNbO 4 :Ho 3+ ,Yb 3+ phosphor, as shown in Fig. 3(a), in which optimization was performed to get intense UC emission by varying the concentrations of Ho 3+ and Yb 3+ ions, shown in the inset of the gure.…”
Section: Optical Behaviormentioning
confidence: 99%
“…GdNbO 4 is known as a self activated compound which has a charge transfer band (CTB) in the UV region and gives blue emission upon UV excitation. 25,30 In GdNbO 4 , the niobate group [(NbO 4 ) 3− ] acts as a uorescence center in the matrix and gives blue emission under UV excitation. In the previous section, it was observed that there is a broad CTB at 266 nm and also a broad blue emission at 442 nm due to the (NbO 4 ) 3− group since the resonance condition of CET from (NbO 4 ) 3− to Yb 3+ ion is well satised.…”
Section: Quantum Cutting (Qc) Behaviormentioning
confidence: 99%
“…It has been reported in the literature that heating becomes more prominent at higher pump power and multiphonon relaxation increases. 25,26 Due to this, the relaxation from the green-emitting level to a lower-lying redemitting level increases. Thus, the intensity of red emission increases.…”
Section: Acs Omegamentioning
confidence: 99%